Effective communication in internal organization at Muehlbauer Technologies Sdn Bhd / Nurul Nadia Mohd Noh - Mohd Noh, Nurul Nadia (Faculty of Business and Management, 2013)
Effective communication in internal organization at Muehlbauer Technologies Sdn Bhd effective communication is very important to an organization. Without a proper communication especially in internal organization may affect the company’s reputation,efficiency and effectiveness. In this report titled ‘Effective Communication in Internal Organization at Muehlbauer Technologies Sdn Bhd’, the researcher will describe the relationship between levels of management, channel communication, information overload and demographic factor with effective communication the company. The objectives of this study are firstly is to examine the relationship between level of management, channel of communication, information overload and demographic factor towards effective communication and also identifying which variable give more significant impact towards effective. These objectives are also for Muehlbauer to improve their efficiency and effectiveness in daily working environment. Throughout this study, a sample of 178 respondents selected from 309 populations in entire level of management in Muehlbauer through stratified random sampling. After data gathered and being analyzed, the result shows that there are significant relationships between independent variables towards the dependant variables. More than that, the researcher also gives some recommendations for future research and also to the practitioner so that they can use and implement it for improving their organization communication. At the end of this study, the researcher found that there are relationships between level of management, communication channel, information overload and demographic factor towards effective communication in Muehlbauer Technologies Sdn Bhd. Thus, all four hypothesis developed are accepted